Pemberdayaan Ekonomi KTH MKK Cisangku Desa Malasari dalam Mengembangkan Persemaian Bibit Tanaman Langka Endemik TNGHS - Karmanah, Karmanah; Rusli, Abdul Rahman; Putra, Mulyana Gustira; Meiganati, Kustin Bintani; Aditya, Fahreza Nur Putra; Nasution, Randy (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The mountain forest area of Mount Halimun Salak National Park (TNGHS) needs to be maintained and protected for its habitat and ecological functions. The existing habitats include Palahlar (Dipterocarpus retusus Blume) and Saninten (Castanopsis argentea), which are rare plants endemic to TNGHS. Currently, its existence is decreasing, so conservation efforts need to be carried out together with the community. Community Partnership Program (PKM) activities aim to increase knowledge to develop KTH MKK Cisangku, especially in the field of seeding rare seeds endemic to TNGHS, as well as increasing the marketing of seeds produced by KTH MKK Cisangku nurseries in order to increase the economic income of its members. PKM activities carried out include socialization, nursery, practical training, digital marketing training, and social media management. Overall, the empowerment of KTH MKK Cisangku, Malasari Village, resulted in an 11.6% increase in the knowledge of its members regarding the development of seed nurseries for rare plants endemic to TNGHS, as well as an expansion of the marketing network for seeds produced by KTH MKK Cisangku nurseries through social media.